The Islamic concept of Minangkabau architectural heritage - Isham Shah; Isdawati Ismail; Mohd Shafrizal Md Hassan (Proceedings of AICS - Social Sciences, 2013)
Islam brings upon harmony and peace to mankind. From an architectural perspective, harmony is valued based on how a space is designed to bring comfort, peace and protection to the occupants. A comfortable home is a basic necessity. The design of a house has to be planned by taking into consideration the physical factors, environment and the major needs of the occupants. Unfortunately, nowadays the design of the modern Malay houses has neglected the factor of harmony which causes discomfort to the occupants. The design of the modern Malay houses no longer takes into consideration factors such as climate, the Malay culture, religious restrictions and the comfort of the occupants. This has consequently produced designs of buildings which are not conducive to be occupants. The solution to this problem is the Malay heritage architecture. This research will look into the benefits of the Malay architecture, specifically the Minangkabau architecture in Negeri Sembilan. The main advantage of the Minangkabau architecture is the ability of the craftsmenin understanding the needs of the environment while designing the houses. The living culture which is Islamic based has blended well among the Malays and the craftsmen have successfully materialised it in designing the Malay houses.Generally, the Minangkabau architecture clearly follows the Islamic concept in providing harmony and comfort to the occupants. This research attempts to see how the Minangkabau architecture has practically applied the Islamic concept in the modern Malay houses to build harmony and comfortable houses in terms of ventilation, the usage of natural sunlight, the design of nature-friendly space and the usage of space to preserve the tradition and culture which is based on Islam. Research is carried out by making comparisons between modern Malay architecture and Minangkabau heritage architecture in relation to the concept of harmony in Islam. The finding of the research could be developed as guidelines in designing houses in Malaysia to provide harmony and comfort to the occupants.Keywords: Architecture, Minangkabau Heritage, Islamic Concept, Harmony, Comfort